Carrier mobility of MoS2 nanoribbons with edge chemical modification. Issue 10 (12th February 2015) - Xiao, Jin; Long, Mengqiu; Li, Mingjun; Li, Xinmei; Xu, Hui; Chan, Kwoksum
Abstract : Charge mobility can be regulated by edge chemical modification in MoS2 ribbons. Abstract : We have investigated the electronic structures and carrier mobilities of MoS2 monolayer sheets and armchair nanoribbons with chemical modification using the density functional theory combined with the Boltzmann transport method with relaxation time approximation. It is shown that the hole mobility (96.62 cm 2 V −1 s −1 ) in monolayer sheets is about twice that of the electron mobility (43.96 cm 2 V −1 s −1 ). The charge mobilities in MoS2 armchair nanoribbons can be regulated by edge modification owing to the changing electronic structures. In pristine armchair nanoribbons, the electron and hole mobilities are about 30 cm 2 V −1 s −1 and 25 cm 2 V −1 s −1, respectively. When the edges are terminated by H or F atoms, the hole mobility will enhance obviously even 10 times that in pristine ribbons, and the electron mobility is comparable with that in MoS2 sheets.